Modelagem formal, simulação e análise em redes de Petri coloridas da realização de atividades laboratoriais a distância presentes no framework ubiquitous lab for practical activities (u-LabPA) - Pequeno Filho, Paulo de Tarso Cavalcante (2016)
Ubiquitous Computing is an area that relates technologies and concepts such as Pervasiveness, Mobility, Adaptability and Location-Oriented Applications. Among the technologies that stand out today in this area there are Wireless Sensor Networks and Radio Frequency Identification Networks, which are being used together to monitor and identify objects and people. Within the scope of Ubiquitous Computing, there are Ubiquitous Laboratories (u-Lab) which are laboratories that have sensing, provision of software services to support the user, support to the performance of activities, among other characteristics. In order to offer support to practices performed in Ubiquitous Laboratories a framework called Ubiquitous Laboratory for Practical Activities (u-LabPA) was created, which allows students to collect data from laboratory activities and to access them later in the form of simulations or virtual environments. In this work we perform the formal modeling and simulation using Colored Petri Nets (RdPC), as well as the analysis of the results of the requisits "Authentication", "Register Activity", "Register User Activity", “Provide User Activities”, "Perform Activity", present in the u-LabPA framework. The results of this analysis reveal that the activity flow of the u-LabPA framework met its basic requirements as well as the stress tests for which it was submitted, maintaining its consistency and its behavior within the expected spectrum.